Strategies to Counter Extremism and Radicalisation in Swedish Schools – Managing Salafi Jihadists Attempts to Influence Students - Falkheimer, Jesper (Scandinavian Journal of Public Administration, 2022)
This article focuses on the importance that municipal schools have, and potentially can have, in counteracting radicalisation in relation to Salafist-Jihadist extremism in Sweden. The purpose of the study is to provide a review of previous research into radicalisation, with a specific focus on the role of schools. In addition to the review, there is a minor qualitative interview study with teachers and experts, which has the aim of creating a dialogue in relation to the research problem. Previous research and the interviews show that there are clear signs of anti-democratic views and values in Swedish schools, especially antisemitism and homophobia. A four-field model illustrates different approaches to radicalisation in schools. Repression is something that is primarily dealt with by law and security agencies, however there is no legal support in Sweden for school management or teachers to identify and report students suspected of radicalisation. In the main, the interviewees supported an active, open and critical dialogue as the right strategy. This is also supported by much of the research on radicalisation. It is important that teachers are well-read and have the courage to raise issues that can be seen as controversial by some students. According to several of the teachers, this is not self-evident in a Swedish context where open conflicts of opinion disrupt consensus.